2021
DOI: 10.21037/atm-21-2721
|View full text |Cite
|
Sign up to set email alerts
|

RAB5C, SYNJ1, and RNF19B promote male ankylosing spondylitis by regulating immune cell infiltration

et al.

Abstract: Background: This study aimed to identify the key genes related to male ankylosing spondylitis (AS) and to analyze the role of immune cell infiltration in the pathological process of this disease. Methods:The AS dataset was downloaded from the Gene Expression Omnibus (GEO) public database, and the data of male healthy controls (M_HC) and male AS patients (M_AS) were extracted. R software was used to identify differentially expressed genes (DEGs). Functional and pathway enrichment analysis of the DEGs was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…A substantial difference in expression of these two genes between AS patients and healthy control individuals and a significant positive connection between them and the neutrophil count were observed 128 . In addition, Zhang et al recently identified key DEPGs expressed in male AS patients including RAB5C, SYNJ1, and RNF19B, which may influence the development and occurrence of AS through influencing activities of immune cells like monocytes and macrophages 129 . MAPK7 and NUDFS4 were two significant contributors in the control of inflammatory response via the TGF‐β pathway through the cAMP‐mediated signaling pathway, and they may be potential target genes for indomethacin 126 .…”
Section: Discussionmentioning
confidence: 99%
“…A substantial difference in expression of these two genes between AS patients and healthy control individuals and a significant positive connection between them and the neutrophil count were observed 128 . In addition, Zhang et al recently identified key DEPGs expressed in male AS patients including RAB5C, SYNJ1, and RNF19B, which may influence the development and occurrence of AS through influencing activities of immune cells like monocytes and macrophages 129 . MAPK7 and NUDFS4 were two significant contributors in the control of inflammatory response via the TGF‐β pathway through the cAMP‐mediated signaling pathway, and they may be potential target genes for indomethacin 126 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous bioinformatics studies have provided data supporting our hypothesis. Zhang et al compared gene expression profiles between male AS patients ( n = 27) and matched healthy controls ( n = 10) in GSE73754, and identified that key genes in AS pathogenesis also regulated immune-cell functions [ 59 ]. That study also showed that the ferroptosis pathway is a significantly enriched term through a gene set enrichment analysis of KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported hazard ratios ranging from 1.75 to 1.82 ( p < 0.001) for the development of Parkinson’s disease (PD) and parkinsonism in AS population [ 78 , 79 ]. Mitochondrial dysfunctions, particularly abnormal oxidative phosphorylation, and epithelial barrier disruption in the gut may be the mechanisms underlying the clinical association between AS and PD [ 59 , 80 , 81 ]. In addition, complex interactions between the ubiquitin-proteasome system and cellular degradation, which participate in autophagy-dependent ferroptosis and progression of AS, may be another possible link between ferroptosis and AS [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA analysis is a systematic biological method used to describe the expression association patterns of different genes in samples 18 . It aggregates genes with highly correlated expression into different modules to explore the association between different modules and sample phenotypes 19 .…”
Section: Methodsmentioning
confidence: 99%
“…WGCNA analysis is a systematic biological method used to describe the expression association patterns of different genes in samples. 18 It aggregates genes with highly correlated expression into different modules to explore the association between different modules and sample phenotypes. 19 By referring to R packages such as limma and WGCNA, 20 we first input the corrected total gene expression matrix, SDEGs list and clinical data into R software, sorted out and extracted the relative expression of SDEGs in each sample, and clustered all SDEGs and samples by hierarchical clustering method based on Pearson correlation.…”
Section: Wgcna For Sdegsmentioning
confidence: 99%